2020
DOI: 10.1017/cts.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

A REDCap-based model for electronic consent (eConsent): Moving toward a more personalized consent

Abstract: Introduction: The updated common rule, for human subjects research, requires that consents “begin with a ‘concise and focused’ presentation of the key information that will most likely help someone make a decision about whether to participate in a study” (Menikoff, Kaneshiro, Pritchard. The New England Journal of Medicine. 2017; 376(7): 613–615.). We utilized a community-engaged technology development approach to inform feature options within the REDCap software platform centered around collection and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 25 publications
0
86
0
Order By: Relevance
“…E-consent allows researchers to present consent information that is enhanced with audio-visual or interactive features [ 8 ]. This could even extend to the use of videos or photographs so participants are able to “meet” the research team.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E-consent allows researchers to present consent information that is enhanced with audio-visual or interactive features [ 8 ]. This could even extend to the use of videos or photographs so participants are able to “meet” the research team.…”
Section: Discussionmentioning
confidence: 99%
“…websites or tablets) and/or digital media (e.g. videos, audio) to enhance the presentation of information, and enable prospective research participants to give informed consent for recruitment [ 7 , 8 ]. A variety of e-consenting approaches can be used simultaneously, offering versatility to researchers who can customise them to suit their project’s needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the majority of CTSA organizations use Docusign As eConsent is conducted through individual secure login accounts, there may be insufficient tracking of virtual versus in-person consent and data capture to support robust comparisons. Vanderbilt's eConsent (REDCap eConsent framework) is the dominant source for a low-cost eConsent platform within the Consortium (11).…”
Section: Data Terminology Standardsmentioning
confidence: 99%
“…Details of the STRIDE eConsent component have been published elsewhere 26 . Briefly, we utilized the REDCap (Research Electronic Data Capture) platform 33 to create a web-based eConsent platform that includes tools that can be customized for a specific study.…”
Section: Enhanced Econsentmentioning
confidence: 99%